Clinico-Epidemiological Profile and Outcome of Poisoning in Children Presenting at a Tertiary Care Hospital of Eastern Nepal - Giri, Arun; Sah, Vijay Kumar; Yadav, Sunil Kumar; Yadav, Niraj (Journal of Nobel Medical College, 2023)
Background: Pediatric poisoning is common emergency worldwide and represents major and preventable cause of morbidity and mortality in children. The study describes epidemiology and outcome of acute poisonings in children presenting to Nobel Medical College through Emergency and Outpatient department and determines causative agents and characteristics of acute poisoning in several pediatric age groups.Material and Methods: This was hospital based prospective cross-sectional study which included all acutely poisoned patients under 18yrs age of either sex who presented to Nobel Medical College Teaching Hospital during 1year period (January 2021 to December 2021). Various socio-demographic variables, poisoning details, clinical manifestations, treatment given, outcome and complications were entered in predesigned proforma. Data was entered in excel sheet and descriptive analysis was done using SPSS software (version 20).Results: During the study period total 56 children with poisoning were admitted and enrolled.  The mean age (±SD) of children with poisoning was 8.18 ± 5.50 Years. Poisoning cases werepredominant in male children (n=56, 53.6%). The most common poison wasorganophosphates(OP) compounds (41.1%). More than three-fourth of cases (92.9%) were symptomatic where nausea/vomiting (78.6%) was most common clinical symptoms, About 83.9% children survived, 10.7% expired and 5.4% left against medical advice (LAMA). Complications were seen in about 37.5% where shock was most common complicationsConclusion: Poisoning was common in adolescent age group.Overall nature of poisoning was accidental however, in adolescent age group majority of them were suicidal in nature.Organophosphates (OP) compounds was most common type of poisoning